2020
DOI: 10.1515/cclm-2020-0869
|View full text |Cite
|
Sign up to set email alerts
|

Quality benchmarking of smartphone laboratory medicine applications: comparison of laboratory medicine specialists’ and non-laboratory medicine professionals’ evaluation

Abstract: ObjectivesThere are many mobile health applications (apps) now available and some that use in some way laboratory medicine data. Among them, patient-oriented are of the lowest content quality. The aim of this study was to compare the opinions of non-laboratory medicine professionals (NLMP) with those of laboratory medicine specialists (LMS) and define the benchmarks for quality assessment of laboratory medicine apps.MethodsTwenty-five volunteers from six European countries evaluated 16 selected patient-oriente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…In a similar study, mobile phones use was found to enhance learning outcomes 31 . In accordance with our scope, many studies have addressed this concept 23,30,32,39,40 . Students performance has improved and their GPA indicates the high impact of applying such methods in teaching, especially challenging subjects such as biochemistry.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In a similar study, mobile phones use was found to enhance learning outcomes 31 . In accordance with our scope, many studies have addressed this concept 23,30,32,39,40 . Students performance has improved and their GPA indicates the high impact of applying such methods in teaching, especially challenging subjects such as biochemistry.…”
Section: Discussionsupporting
confidence: 61%
“…31 In accordance with our scope, many studies have addressed this concept. 23,30,32,39,40 Students performance has improved and their GPA indicates the high impact of applying such methods in teaching, especially challenging subjects such as biochemistry. Student perceptions revealed that applications were an effective and innovative tool for learning during the COVID-19 period, based on previous trials of smartphone use.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients are interested in receiving their annotated laboratory medicine results, raising the possibility of direct contact with the laboratory and a new paradigm for laboratory activities [35]. Jovičić et al [36] compared testing result interpretation by some mobile health (mHealth) applications (apps) and advice from laboratory professionals, which confirmed the inefficiency of most current medical apps. The use of integrated technologies in thyroid models has been relatively successful.…”
Section: Interpretation Of Test Resultsmentioning
confidence: 99%
“…Jovičić et al. [36] compared testing result interpretation by some mobile health (mHealth) applications (apps) and advice from laboratory professionals, which confirmed the inefficiency of most current medical apps. The use of integrated technologies in thyroid models has been relatively successful.…”
Section: Construction Of a Patient‐centered Medicine System Through T...mentioning
confidence: 99%
“…By applying information management technology to analyse and monitor the time nodes of key links in laboratory tests, the main test line, namely the “laboratory test report”, can be more effectively managed. Although IT has been applied to laboratory management and achieved favourable results [ 12 14 ], transformation and optimisation based on this technology are performed differently according to the procedures of individual hospitals. Hence, it is necessary to incorporate IT into the overall emergency laboratory test process and constantly conduct summarisations and optimisations in clinical practice, thereby maximising automation and early warning during each step.…”
Section: Introductionmentioning
confidence: 99%